GONADAL DYSFUNCTION WITH POSTPRANDIAL HYPERTRIGLYCERIDEMIA IS RISK PREDICTORS OF CARDIOVASCULAR DISEASE IN MEN WITH TYPE 2 DIABETES MELLITUS (Iraqi Journal of Medical Sciences, 2016)
Background:The association of type 2 diabetes mellitus and risk of cardiovascular disease is well documented. Insulin resistance is the hallmark feature of type 2 diabetes and there is evidence to suggest that testosterone is an important regulator of insulin sensitivity in men, with a role for testosterone in lipid metabolism and specially the triglyceride fraction.Objective:To emphasize the association of low level of total testosterone with that of the postprandial triglyceride in male patients’ with type 2 diabetes mellitus.Methods: Forty two type 2 diabetes mellitus male patients and 42 healthy controls of age range between 30-60 years, during the period from December 2011 to June 2012. Postprandial venous blood used for random blood glucose, lipid profile, urea and creatinine measurement. Luteinizing hormone, follicle stimulating hormone, testosterone, and sex hormone binding globulin was done using Enzyme-Linked Immuno Sorbent Assay (Sandwich assay).Results:A negative correlation between testosterone, and postprandial triglyceride, in both type 2 diabetes mellitus and control groups with a significant difference in testosterone between the two groups. The sex hormone binding globulin was also correlated negatively with postprandial triglyceride in only the control group.Conclusion: Hypogonodism in male (decline in testosterone level) leads to increased postprandial hypertriglyceridemia, which could, both, be considered of predictors for cardiovascular disease risk factors in male patients with type2 diabetes mellitus.Key words:Postprandial triglycerides, type2 diabetes mellitus, testosterone.
Keywords: Postprandial triglycerides; type2 diabetes mellitus; testosterone